(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2025)
This article examines the moral dimensions embedded within English paremias (proverbs) and their role in shaping cultural perceptions of individualism and personal freedom. By analyzing a selection of widely used English proverbs, the study identifies conceptual metaphors and value-laden oppositions that reflect and reinforce Western ideals of self-reliance, autonomy, and personal responsibility. The research highlights how these linguistic expressions not only mirror social norms but also contribute to the moral framework through which individuals interpret their roles within society. Through a discourse-analytical and conceptual approach, the article reveals that English paremias serve as vehicles of cultural transmission, promoting ethical attitudes toward independence, decision-making, and self-expression. The findings suggest that proverbs are not merely rhetorical devices but powerful tools in the construction of socio-cultural identity and moral outlooks in English-speaking communities.